2017
DOI: 10.1590/1519-6984.08116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roads on the vertebrates diversity of the Indigenous Territory Paresi and its surrounding

Abstract: Roadkill impact is still underestimated due to the lack of knowledge of its intensity and effect on animal populations. To assess differences between animal roadkills on roads in distinct landscapes, this study recorded meso-and megavertebrate roadkills along 50 km during a year in two highways in the transitional area of Amazonia/Cerrado in Tangará da Serra, Mato Grosso: MT-358 and MT-235, the latter crossing the Paresi Indigenous Land. We assessed roadkill rates and points with higher rates of roadkills, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
3
13
1
6
Order By: Relevance
“…The black line represents the observed number of neighbors per roadkill along the road minus the mean expected number of neighbors if the roadkill was distributed randomly. Values above the upper confidence limit (grey line) indicate significant clustering of roadkill with those observed in other studies (Brum, Santos-Filho, Canale, & Ignácio, 2018;Coelho et al, 2008;Vargas-Salinas, Delgado-Ospina, & López-Aranda, 2011). However, we found that herpetofauna is affected the most whereas in other studies (Coelho et al, 2008;Miranda et al, 2017;Teixeira, Coelho, Esperandio, Rosa Oliveira, et al, 2013) (Sosa & Schalk, 2016).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The black line represents the observed number of neighbors per roadkill along the road minus the mean expected number of neighbors if the roadkill was distributed randomly. Values above the upper confidence limit (grey line) indicate significant clustering of roadkill with those observed in other studies (Brum, Santos-Filho, Canale, & Ignácio, 2018;Coelho et al, 2008;Vargas-Salinas, Delgado-Ospina, & López-Aranda, 2011). However, we found that herpetofauna is affected the most whereas in other studies (Coelho et al, 2008;Miranda et al, 2017;Teixeira, Coelho, Esperandio, Rosa Oliveira, et al, 2013) (Sosa & Schalk, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…The higher the intensity (red color) the higher the aggregation of roadkill vertebrates such as frogs and small snakes are therefore more easily missed than mammals, which tend to be larger (D'Anunciação, Lucas, Silva, & Bager, 2013;Santos et al, 2016;Slater, 2002). This could also partially explain the relatively high roadkill per surveyed km in this study compared to estimates by Brum et al (2018) and Payan et al (2013). Finally, the persistence time of carcasses is generally lower for reptiles and amphibians than for mammals (Santos, Carvalho, & Mira, 2011), which may also have led to an underestimation of reptile and amphibian mortality in other Neotropical studies, performed with a longer sampling interval (e.g., a week).…”
Section: Discussionmentioning
confidence: 52%
“…However, this animal is very selective in its choice of habitat and is dependent on forest cover and wet areas (Desbiez et al, 2009). The high frequency of roadkill records (Cherem et al, 2007;Cunha et al, 2010;Costa, 2011;Caceres et al, 2012) may be due to its limited sight and hearing as well as its exposure during slow movements between forest fragments intercepted by roadways (Brum et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on the effect of seasonality on mammals killed by vehicular traffic (Carvalho et al, 2017), studies demonstrate a correlation between vehicle-related deaths (roadkills) of wild mammals and seasonality (Brum et al, 2017), which is likely associated with dispersal and migration movements related to foraging and reproduction (Braz & França, 2016).…”
Section: Iheringia Iheringiamentioning
confidence: 99%
“…Both species are common and adapted to living in disturbed environments, they are omnivorous and even eat dead animals on the road, the same being true for Conepatus semistriatus (Reis et al, 2010). The BR-050 highway presented a roadkill rate of 0.03 wild mammals/km/day which is relevant when compared to other researchers performed in a Cerrado region, 0.01 (Cunha, Moreira, & Silva, 2010;Carvalho, Bordignon, & Shapiro, 2014), 0.02 (Braz & França, 2016); 0.03 (Cáceres et al, 2012;Brum et al, 2018). Anyway, roadkill rates are underestimated and a correction index needs to be calculated in order to try to get more actual numbers (Santos, Carvalho, & Mira, 2011;.…”
Section: Discussionmentioning
confidence: 81%